Regenerasi Tanaman pada Kultur Antera Beberapa Aksesi Padi Indica Toleran Aluminium - Iswari S. Dewi; Bambang S. Purwoko; Hajrial Aswidinnoor; Ida H. Somantri; M. A. Chozin (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2006)
Anther culture provides the quick route in obtaining pure lines in a single generation from either green haploid plant that may be artificially or spontaneously doubled. Indica rice known as recalcitrant genotype because of its difficulty in regenerating sufficient number of green plantlets among the regenerated plants through anther culture. Whilst, research on studying anther culture ability has to be done to assure the success of rice breeding through anther culture. The objective of this research was to determine regeneration ability of five accessions of indica rice tolerance to aluminum through application of putrescine in anther culture. Completely randomized design with 15 replications was used in this research. Treatments consisted of five accessions of aluminum tolerance indica rice, ie. CT6510-24-1-3, Grogol, Hawara Bunar, Krowal, and Sigundil. Callus induction medium based on N6 medium + 10-3 M putrescine, while regeneration medium based on MS + 10-3 M putrescine. The results indicated that culture ability is controlled by the genotype. From this research, Grogol, Krowal and Sigundil were selected as accessions having good rice anther culture ability, and therefore can be used as parents for developing new rice varieties tolerance to aluminum through anther culture.